НОВЫЕ ИНФОРМАЦИОННЫЕ РЕШЕНИЯ В АСУ ТЕХНОЛОГИЧЕСКИМ КОМПЛЕКСОМ ПОВЕРХНОСТИ ШАХТЫ - Киктев, Н. А.; Чичикало, Н. И.; Ларина, Е. Ю. (Енергетика і автоматика, 2017)
NEW INFORMATION SOLUTIONS IN ACS TECHNOLOGICAL COMPLEX SURFACE OF THE MINE N. Kiktiev, N. Chichikalo, K. Larina For the smooth operation of complex technological lines equipped with mining transport, an important role is played by the possibility of temporary accumulation of material. This is done in order to exclude emergency situations in case of violation of the temporary characteristics of individual equipment or short-term malfunctions in the continuous transport chain. The rock complex refers to the technological objects of the mine with a low level of automation. This object often uses inefficient manual control, which leads to significant material costs, and does not exclude emergency situations. The purpose of the study is to increase the efficiency of managing the technological process of transporting cargo traffic when discharging rock to dumps by building a cognitive system for displaying the process control system, reducing energy costs, and economic costs by automatically measuring the mass of rock in the trolley while unloading the hopper. The choice of the configuration of the rock transport system to the heap is based on local conditions: the situational plan, the transportation distance, the capacity, the productivity and service life of the dumps, the moisture content and the size of the transported rock, and the technical and economic indicators. In order to take into account the productivity of rock dumps, it is also necessary to know the amount of the exported rock to the heap. Monitoring this parameter allows you to:  uniform distribution of rock masses in the worked-out area of quarries, crumbling zones, ravines, ravines, etc.  orientation of the unloading process taking into account the leeward side of the population centers and industrial sites in order to reduce damage to the environment;  normal operation of the winch, as overloading the trolleys causes excessive stress on the engine and rope, which can lead to unforeseen economic costs for equipment repairs. The information from all the sensors goes to the UZTV device, which processes the received information, generates control actions, and also transfers information to the console of the mountain dispatcher, which has a mnemonic diagram, the dispatcher’s industrial computer, the equipment control panel, and the operational communication device. The process of rock transportation can be carried out automatically, taking into account all parameters and forming commands for automatic control of the hopper’s shutter, the operation of the conveyor and movement of the trolley to the loading and unloading points, and remotely by the operator via the control and display panel or from the dispatcher’s console. New in the proposed system is the automatic measurement of the rock mass in the trolley when unloading the hopper. Measurement of the mass of the rock in the trolleys is necessary for the normal operation of the winch, since when the trolleys are overloaded, the engine, rope is excessively loaded, which leads to unnecessary energy costs, to economic costs if any of the elements included in the winch fail. The principle of operation of this automated system is that it becomes possible to minimize the human impact on loading and transport operations, accelerate the loading process, increase the accuracy of determining the transported rock mass and record it. Conclusions. 1. The developed algorithm makes it possible to minimize the human impact on loading and transport operations, to accelerate the loading process, to increase the accuracy of determining the transported rock mass and to account for it. 2. When working with real objects, this algorithm can be used as an independent system, and as part of similar automated control systems.